Comparisons of Two Proteomic Analyses of Non-Mucoid and Mucoid Pseudomonas aeruginosa Clinical Isolates from a Cystic Fibrosis Patient - Rao, Jayasimha; Damron, F. H.; Basler, Marek; DiGiandomenico, Antonio; Sherman, Nicholas E.; Fox, Jay W.; Mekalanos, John J.; Goldberg, Joanna B. (Frontiers in Microbiology, 2011)
Pseudomonas aeruginosa chronically infects the lungs of cystic fibrosis (CF) patients. The conditions in the CF lung appear to select for P. aeruginosa with advantageous phenotypes for chronic infection. However, the mechanisms that allow the establishment of this chronic infection have not been fully characterized. We have previously reported the transcriptional analysis of two CF isolates strains 383 and 2192. Strain 2192 is a mucoid, alginate overproducing strain whereas strain 383 is nonmucoid. Mucoid strains are associated with chronic infection of the CF lung and nonmucoid strains are the typical initially infecting isolates. To elucidate novel differences between these two strains, we employed two methods of shotgun proteomics: iTRAQ (Isobaric Tags for Relative and Absolute Quantitation) and two-dimensional (2-DE) gel electrophoresis. iTRAQ compares the amount of protein between samples and relies on protein abundance, while 2-DE gel electrophoresis depends on selection of separated protein spots. For both these methods, mass spectrometry was then used to identify proteins differentially expressed between the two strains. The compilation of these two proteomic methods along with Western blot analysis revealed proteins of the HSI-I operon of the type 6 secretion system, showed increased expression in 383 compared to 2192, confirming the our previous transcriptional analysis. Proteomic analysis of other proteins did not fully correlate with the transcriptome but other differentially expressed proteins are discussed. Also, differences were noted between the results obtained for the two proteomic techniques. These shotgun proteomic analyses identified proteins that had been predicted only through gene identification; we now refer to these as “proteins of unknown functions” (PUFs) since their existence has now been established however their functional characterization remains to be elucidated.